Pengaruh Penggunaan Model Make A Match Terhadap Hasil Belajar Siswa Pada Pembelajaran Ipa Kelas Iv Sdn 5 Kayumalue Ngapa - Thalib, nurafni; Nuraini, Nuraini (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2022)
This study aims to determine the Effect of Using the Make a Match Model on Science Learning for Grade IV of SDN 5 Kayumalue Ngapa. This type of research is quantitative research with One Group Pre-test-Post-test Design. 12 grade IV students were involved as the population. The sampling technique was 12 students consisting of 7 male students and 5 female students. The data collection technique in this study was in the form of a multiple-choice test. The results of this study showed that the average pre-test was 55.83 while the average post-test was 80.83. Based on the research that has been carried out in grade IV of SDN 5 Kayumalue Ngapa, the data obtained from the calculation of hypothesis testing at a real level of 5% (0.05) obtained a t_count value of 7.00. t_count> t_table or 7.00> 2.201 because it is known that t_count> t_table then Ha is accepted and Ho is rejected. So it can be concluded that there is an influence of the make a match model on student learning outcomes in science learning in class IV SDN 5 Kayumalue Ngapa.